Administration of intestinal mesenchymal stromal cells reduces colitis-associated cancer in C57BL/6J mice modulating the immune response and gut dysbiosis - Laura Hidalgo-García; Antonio Jesús Ruiz-Malagon; Francisco Huertas; María Jesús Rodríguez-Sojo; José Alberto Molina-Tijeras; Patricia Diez-Echave; Patricia Becerra; Benito Mirón; Rocío Morón; Alba Rodríguez-Nogales; Julio Gálvez; María Elena Rodríguez-Cabezas; et al. (Elsevier, 2023)
Background: Patients with inflammatory bowel disease (IBD) have a higher risk of developing colitis-associated colorectal cancer (CAC) with poor prognosis. IBD etiology remains undefined but involves environmental factors, genetic predisposition, microbiota imbalance (dysbiosis) and mucosal immune defects. Mesenchymal stromal cell (MSC) injections have shown good efficacy in reducing intestinal inflammation in animal and human studies. However, their effect on tumor growth in CAC and their capacity to restore gut dysbiosis are not clear. Methods: The outcome of systemic administrations of in vitro expanded human intestinal MSCs (iMSCs) on tumor growth in vivo was evaluated using the AOM/DSS model of CAC in C57BL/6J mice. Innate and adaptive immune responses in blood, mesenteric lymph nodes (MLNs) and colonic tissue were analyzed by flow cytometry. Intestinal microbiota composition was evaluated by 16S rRNA amplicon sequencing. Results: iMSCs significantly inhibited colitis and intestinal tumor development, reducing IL-6 and COX-2 expression, and IL-6/STAT3 and PI3K/Akt signaling. iMSCs decreased colonic immune cell infiltration, and partly restored intestinal monocyte homing and differentiation. iMSC administration increased the numbers of Tregs and IFN-γ+CD8+ T cells in the MLNs while decreasing the IL-4+Th2 response. It also ameliorated intestinal dysbiosis in CAC mice, increasing diversity and Bacillota/Bacteroidota ratio, as well as Akkermansia abundance, while reducing Alistipes and Turicibacter, genera associated with inflammation. Conclusion: Administration of iMSCs protects against CAC, ameliorating colitis and partially reverting intestinal dysbiosis, supporting the use of MSCs for the treatment of IBD.